A comparative study of three groups of ductile fracture loci in the 3D space. (February 2015) - Bai, Yuanli; Wierzbicki, Tomasz
Highlights: Fracture loci of 16 ductile fracture models are compared in 3D & 2D spaces. Some implicit features of these models are revealed. Gurson type fracture models are plot in 3D locus under proportional conditions. The existence of cutoff region of ductile fracture models is discussed. The differences of second stress state parameter are compared and discussed. Abstract: Ductile fracture is inherently a three-dimensional phenomenon and should be represented in the 3-D space. Sixteen fracture models are evaluated and divided into three groups: physics based models, phenomenological models and empirical models. These models are then calibrated from the three sets of experimental data, TRIP 690 and TRIP 780 steel sheets and 2024-T351 aluminum alloy. Under the assumption of monotonic loading conditions, major qualitative differences emerged from the comparison of the models in terms of the range of applicability as well as shapes of the 3D fracture envelope are discussed. Several implicit features of these models are revealed.